(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The paper considers the problem of forming a vocabulary and compiling dictionaries in common in the territory of Ukraine of the Ukrainian-Russian language interference.